Cooperatives in the Midst of Digitalization: Dignity and Compliance of Cooperative Managers in Cirebon with the Cooperative Law - Nurkholiza, Disya Dwi Ajeng; Guntoro, M (Faculty of Law Universitas 17 Augustus 1945 Cirebon, 2024)
The purpose of this study is to explore how cooperatives can maintain dignified values and comply with cooperative laws in the face of digitalization. The background of this research problem focuses on the challenges faced by cooperatives in maintaining their core principles, such as solidarity and social justice, amidst rapid technological development. The novelty of this research lies in combining the analysis of cooperative values with the application of digital technology and its impact on compliance with applicable cooperative regulations. The methodology used in this research is a qualitative approach with case studies on several cooperatives that have adopted digital technology, as well as in-depth interviews with cooperative managers and cooperative law experts. The results show that although digitalization provides operational convenience and market access, most cooperatives still face obstacles in implementing policies that are in line with cooperative principles, as well as meeting existing legal obligations. The economic implications of this research show that cooperatives that successfully integrate digitalization with dignified values can improve their competitiveness, expand member networks, and create jobs, while strengthening the local economy through a more efficient and transparent system.